Silver nanowire as an efficient filler for high conductive polyurethane composites. Issue 4 (4th March 2019) - Al-Attabi, Nuha Y.; Adhikari, Raju; Cass, Peter; Bown, Mark; Gunatillake, Pathiraja A.; Malherbe, François; Yu, Aimin
ABSTRACT: Composites of silver nanowires (AgNWs) and polyurethane (PU) were prepared and their properties evaluated for potential applications as electrically conducting materials. Polyurethanes were chosen as the base substrate because of their inherent biocompatibility, biostability, excellent processability and good mechanical properties. The composites were prepared with varying content of AgNW by a solvent casting method. The electrical conductivity of the resulting composites was assessed using a 4-probe conductivity method and a maximum conductivity of 352.6 S cm –1 was achieved with 25% AgNW loading. The composite films were then characterised by various techniques to investigate the structure–property relationships. The above-mentioned analyses showed that the composite films retained the tensile and thermal properties of the parent PU while showing excellent conductivity.